Communication technology and the television industry in Malaysia / Mokhtar Muhammad - Muhammad, Mokhtar (Faculty of Communication and Media Studies (FCMS), 2008)
The rapid development of technology in the media is surely one of the signs of progress in today's society. In view of these innovations in continuous evolution, the author of the article entitled: "Communication Technology and the Television Industry in Malaysia" discussed how technology helped transformed the 'old' society to the 'new' society.